Applying neurodevelopmental theory to school‐based drug misuse prevention during adolescence. Issue 141 (March 2014) - Riggs, Nathaniel R.; Black, David S.; Ritt‐Olson, Anamara
Abstract : Adolescence is characterized by incredible development in the prefrontal cortex of the brain, which is responsible for behavioral and emotional self‐regulation, and higher order cognitive decision‐making skills (that is, executive function). Typically late prefrontal cortical development and its integration with limbic areas of the brain associated with reward, pleasure, novelty seeking, and emotion can contribute to substance misuse vulnerability during adolescence. In this chapter, literature on the developmental integration of the prefrontal cortex with emotion and motivation centers of the brain is reviewed. Then this research is applied to school‐based adolescent substance misuse prevention, highlighting two examples of preventive interventions incorporating neurocognitive models into comprehensive prevention approaches. Finally, innovative strategies (for example, mindfulness training) for promoting neurocognition as a mediator to substance misuse vulnerability are discussed.